Prospective Study of lncRNA NORAD for Predicting Cerebrovascular Events in Asymptomatic Patients with Carotid Artery Stenosis - Yan Fan; Yan Ma; Rui Wang; Lili Wang (Clinical and Applied Thrombosis/Hemostasis)
Background Carotid artery stenosis (CAS) may cause many cerebrovascular diseases, and a biomarker for screening and monitoring is needed. This study focused on the clinical significance of long-chain non-coding RNA (lncRNA) non-coding RNA activated by DNA damage (NORAD) in patients with CAS and aimed to search for potential biomarkers of CAS. Methods Eighty-six asymptomatic patients with CAS and 60 healthy individuals were enrolled, with corresponding clinical data and serum samples collected. The expression of NORAD was detected by reverse transcription-quantitive PCR (RT-qPCR). All patients were followed up for 2 years to collected the occurrence data of cerebrovascular events, and Kaplan-Meier and Cox regression were used for data analysis. Receiver operator characteristic curve was used to analyze the diagnostic value of NORAD in distinguishing CAS patients from healthy people, and to evaluate the prediction accuracy of NORAD. Results NORAD is overexpressed in the serum of CAS patients, and associated with patients’ hypertension, TC, LDL-C levels and stenosis degree. NORAD has high sensitivity (88.37%) and specificity (80.00%) in the identification of CAS patients (AUC = 0.917). NORAD was independently related to the occurrence of cerebrovascular events (HR = 2.435, P  = .003). a logistic regression risk model for predicting cerebrovascular events was constructed with the parameters including NORAD, TC and LDL. Conclusion NORAD can be used as a diagnostic and prognostic biomarker for CAS, and NORAD, total cholesterol (TC), and low density lipoprotein cholesterol (LDL-C) can be independently correlated to predict cerebrovascular events.